EVOLVING PREDICTOR VARIABLE ESTIMATION MODEL FOR WEB ENGINEERING PROJECTS - Kumar Srivastava, Sanjay; Prasad, Poonam; Varma, S.P. (Covenant Journal of Informatics and Communication Technology, 2016)
The field of web cost estimation is an important area which has not received much attention and has been the reason of failure of a number of web projects. Early web cost estimation can save disastrous situation. In this paper a review of previous work done in the field of web estimation like Size measures of Cowderoy, Mendes et al., Rollo and Cleary has been made. It further narrates Mendes Web Cost estimation Model, Tukutuku Project and derivation of effort equation. The paper investigates the applicability verification survey of web projects developed by Indian companies. The verification results being favorable Evolving Predictor Variable Estimation Model for Web Engineering Projects has been framed on the basis of curve fitting by sums of exponentials using Froberg’s method and Moore’s method. The model takes into the strength of development team as predictor variable and gives the gross effort in hours worked by taking into account the additional issues of contingencies, risk management and profitability issues which were neglected by Mendes et al. while creating their Early Web Cost Estimation Model. It further calculates the Current Sale Price of the web based project based on the development team in Indian Rupees (INR) at the 2014 price level. The early web effort and cost prediction has thus become more accurate and shall be advantageous at the project enquiry and bidding stage.